IMPLEMENTATION OF E-LEARNING: NEEDS AND POSSIBILITIES (BASED ON THE RESULTS OF SOCIOLOGICAL SURVEY) - Bohomaz, Kostiantyn; Sorokina, Liudmyla; Shelomovska, Oksana; Romaniukha, Maryna (Електронне наукове фахове видання “ВІДКРИТЕ ОСВІТНЄ Е-СЕРЕДОВИЩЕ СУЧАСНОГО УНІВЕРСИТЕТУ”, 2016)
The article analyzes students’ replies to a poll on topical issues of introduction of electronic education. The poll represents an instrument of research into aspects of e-learning within European project IRNet — “International Research Network for study and development of new tools and methods for advanced pedagogical science in the field of ICT instruments, e-learning and intercultural competences”. In particular, the article looks into information competence, the commitment and the willingness of students to study in e-learning system are defined. It is proved that the use of elements of e-learning is a topical alternative teaching method and the essential support to traditional education. The article presents general requirements for distance learning systems and organizational actions that must precede the process of their implementation.